RANCANGAN MESIN PEMOTONG ADONAN KERUPUK GETAS - Dani Ismarini; Marini; Muhammad H Amrullah; Indah R Pratiwi (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Getas crackers are one of the crackers that are in great demand by the public. Getas itself is produced in two forms some are elongated, and some are round. There are still many brittle cracker processing places that produce brittle manually, so that is the basis for the idea of this